Asuhan Keperawatan Pasien Dengan Harga Diri Rendah Kronis Kronis Di RSUD Prof Dr Soerojo Magelang - Ratnaningrum, Nitri; Isma Sundari, Ririn (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Schizophrenia is a multifaceted disorder that affects the brain, causing disturbances in thought, perception, emotion, movement, and behavior. In patients diagnosed with schizophrenia, several nursing problems have been identified, including low self-esteem. Low self-esteem is defined as a negative sense of self. The etiology of this problem is multifactorial, with potential contributors including repeated failures, past trauma, experiences of rejection or not being accepted, and loss. The objective of this study was to delineate the nursing care for schizophrenic patients grappling with low self-esteem and nursing complications. The research employed a case study design, utilizing a nursing approach. The sample population comprised a single patient. The objective of this study was to ascertain the most efficacious nursing care for cases of low self-esteem in patients by implementing the strategy (SP) over the course of three meetings. The findings of the study indicated that on the third day following the implementation of the SP1-SP3 protocol, the subject's low self-esteem exhibited a partial resolution. The patient reported a shift in their sense of self-worth, stating that they no longer perceived themselves as useless. However, they continued to experience a sense of embarrassment when interacting with others. The patient demonstrated an increased inclination toward making eye contact, speaking in a more deliberate and gentle manner, and engaging in interactions with others.